2006
DOI: 10.1074/jbc.m512700200
|View full text |Cite
|
Sign up to set email alerts
|

Regions of the Catalytic α Subunit of Na,K-ATPase Important for Functional Interactions with FXYD 2

Abstract: The ␥ modulator (FXYD 2) is a member of the FXYD family of single transmembrane proteins that modulate the kinetic behavior of Na,K-ATPase. This study concerns the identification of regions in the ␣ subunit that are important for its functional interaction with ␥. An important effect of ␥ is to increase K ؉ antagonism of cytoplasmic Na ؉ activation apparent as an increase in K Na at high. We show that although ␥ associates with ␣1, ␣2, and ␣3 isoforms, it increases the K Na of ␣1 and ␣3 but not ␣2. Accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…However, in contrast to our findings with PLM, E960A-NKA mutation does not alter regulation of the pump's apparent Na + affinity by FXYD2 and FXYD4 (18). One study (21) suggested that the structural association of TM9 with FXYD2 TM domain is not the sole determinant of the FXYD2 effect on the apparent Na + affinity. The authors pointed out that long-range modulation by the extracellular loop between TMs 7 and 8 is also involved (21).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…However, in contrast to our findings with PLM, E960A-NKA mutation does not alter regulation of the pump's apparent Na + affinity by FXYD2 and FXYD4 (18). One study (21) suggested that the structural association of TM9 with FXYD2 TM domain is not the sole determinant of the FXYD2 effect on the apparent Na + affinity. The authors pointed out that long-range modulation by the extracellular loop between TMs 7 and 8 is also involved (21).…”
Section: Discussioncontrasting
confidence: 56%
“…One study (21) suggested that the structural association of TM9 with FXYD2 TM domain is not the sole determinant of the FXYD2 effect on the apparent Na + affinity. The authors pointed out that long-range modulation by the extracellular loop between TMs 7 and 8 is also involved (21). Such fine differences in the FXYD-NKA-α structural interaction may underlie the intrinsic differences in NKA modulation among various FXYDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicate that the transmembrane domain of FXYD2 binds to the groove formed by M2, M6, and M9 of the Na,K-ATPase α-subunit [11], whereas the location of the cytoplasmatic part is still questionable [12]. In addition, it appears that the extracellular loop between M7 and M8 is the focal region for γ-α-β interactions [13]. Mahmmoud et al [14] could isolate FXYD2 oligomers when the detergent sodium dodecylsulphate (SDS) was replaced by perfluoro-octanoic acid (PFO, a detergent that tolerates weak interactions) during polyacrylamide gel electrophoresis.…”
Section: Introductionmentioning
confidence: 99%